'And Who Is My Parishioner?' Residency, Human Rights and the Right to Burial in the Parish Churchyard. (January 2022) - Burrell, Andrew
Abstract : When asked by an expert in the law, 'And who is my neighbour?', Jesus answered with the parable of the good Samaritan (Luke 10:25–37). This was a radically inclusive answer: your neighbour could be anyone. By contrast, a priest who asks an ecclesiastical lawyer 'and who is my parishioner?' may be given a far less clear or satisfying answer.